2022
DOI: 10.1038/s41392-022-00939-7
|View full text |Cite|
|
Sign up to set email alerts
|

NUPR1 promotes the proliferation and metastasis of oral squamous cell carcinoma cells by activating TFE3-dependent autophagy

Abstract: Oral squamous cell carcinoma (OSCC) is the most common type of oral malignancy, and metastasis accounts for the poor prognosis of OSCC. Autophagy is considered to facilitate OSCC development by mitigating various cellular stresses; nevertheless, the mechanisms of autophagy in OSCC cell proliferation and metastasis remain unknown. In our study, high-sensitivity label-free quantitative proteomics analysis revealed nuclear protein 1 (NUPR1) as the most significantly upregulated protein in formalin-fixed paraffin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…ERK phosphorylation modulates autophagy [31,32], and autophagy has been shown to be associated with cell proliferation in cancer cells [33]. Therefore, we speculated that ANGPTL8-mediated activation of the ERK pathway could promote HCC cell proliferation via autophagy.…”
Section: Discussionmentioning
confidence: 95%
“…ERK phosphorylation modulates autophagy [31,32], and autophagy has been shown to be associated with cell proliferation in cancer cells [33]. Therefore, we speculated that ANGPTL8-mediated activation of the ERK pathway could promote HCC cell proliferation via autophagy.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported that NUPR1 is associated with autophagy [24] . Hence, we speculated that NUPR1 may be also implicated in modulating autophagy in CC cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, the occurrence of oral cancer has increased markedly worldwide ( 17 ). OSCC, a common type of oral cancer, has been characterized by a high degree of malignancy and poor prognosis ( 18 ). It has been shown that OSCC has high a potential for metastasis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%